Evaluating the Impact of Ai-Generated Outputs on Student Assessment: Educator's Perspective - Dolba, Sammy Q.; Inoncillo, Frederick A; Nunez, Jayrome L. (International Journal of Artificial Intelligence Research, 2025)
This study investigates educators' perceptions of the impact of artificial intelligence (AI)-)-generated outputs on student assessment in the Philippine educational context. With the rapid integration of AI technologies in education, understanding how educators view these tools is crucial for effective implementation. A descriptive quantitative research design was employed, utilizing a structured survey distributed to a diverse group of 93 educators across various disciplines. The findings reveal a generally positive perception of AI's role in enhancing teaching practices, with a mean score of M = 3.42 indicating high perceived value. However, concerns regarding the reliability and fairness of AI-generated output were noted, with mean scores of M = 3.30 and M = 3.28, respectively. Additionally, educators expressed moderate confidence in using AI tools, reflected by a mean score of M = 3.24. Qualitative responses highlighted ethical considerations and the need for continuous professional development to equip teachers with the necessary skills to effectively integrate AI into their assessments. This research underscores the potential benefits and challenges associated with AI in education, emphasizing the importance of addressing educators' concerns to maximize the advantages of AI technologies in student learning outcomes.